Analysis of Road Performance and Impact on Pasir Putih-Ocarina Bengkong Sadai Road Batam-Indonesia - Malvin Iuryanto; Usmanul Hayadi Umar (LEADER: Civil Engineering and Architecture Journal, 2023)
Jalan Pasir Putih to Ocarina is a highway area that is strategically located because it is in the center of Batam city and this road is often passed by because it is connected to the Batam International Port, tourist attractions, places to eat or food court, malls, government offices, and many more. The advantage that exists on this highway is the efficient travel time from Bengkong to Batam Center it greatly saves travel time. Meanwhile, the weakness of this one highway is that it is prone to accidents, so the level of safety for road users is low. This case study was made to evaluate the road segment's performance level and its impact. The analytical method used is index performance analysis by comparing the performance of the current road segment with the expectations of road users with the performance of that segment. The research results show that the existing road performance average index is 2,36, then the average index of road users' importance is 1,16 and the average GAP index is. The purpose of making this case study is expected to increase the safety and comfort of road users.